Distinct metabolic changes between wheat embryo and endosperm during grain development revealed by 2D‐DIGE‐based integrative proteome analysis. Issue 10 (27th April 2016) - Cao, Hui; He, Miao; Zhu, Chong; Yuan, Linlin; Dong, Liwei; Bian, Yanwei; Zhang, Wenying; Yan, Yueming
Abstract : Two Chinese bread wheat cultivars, Jinghua 9 and Zhongmai 175, distinct in grain weight and dough quality, were used to study proteome changes in the embryo and endosperm during grain development using a two‐dimensional difference gel electrophoresis (2D‐DIGE)‐based proteomics approach. In total, 138 and 127 differentially expressed protein (DEP) spots representing 116 and 113 unique DEPs were identified in the embryo and endosperm, respectively. Among them, 54 (31%) DEPs were commonly present in both organs while 62 (35%) and 59 (34%) DEPs occurred only in the embryo and endosperm, respectively. Embryonic DEPs are primarily stress‐related proteins and involved in carbohydrate and lipid metabolism, while those from the endosperm are related primarily to carbohydrate metabolism and storage. Principal component analysis (PCA) indicated that the proteome differences in the endosperm caused by different cultivars were greater than those by development stages, while the differences in the embryo showed the opposite pattern. Protein‐protein interaction (PPI) analysis revealed a complex network centered primarily on enzymes involved in carbohydrate and protein metabolism. The transcriptional levels of fourteen important DEPs encoding genes showed high similarity between organs and cultivars. In particular, some key DEPs of the endosperm, such as phosphoglucomutase, ADP‐glucose pyrophosphorylase (AGPase), and sucrose synthase (SUS), showed significantly upregulated expression, indicating their key roles in starch biosynthesis and grain yield. Moreover, upregulated expression of some storage proteins in the endosperm could improve wheat bread‐making quality.